Patterns of Focal- and Large-Scale Synchronization in Cognitive Control and Inhibition: A Review - Beppi, Carolina; Violante, Ines R.; Hampshire, Adam; Grossman, Nir; Sandrone, Stefano (Frontiers in Human Neuroscience, 2020)
Neural synchronisation patterns are involved in several complex cognitive functions and constitute a growing trend in neuroscience research. While synchrony patterns in working memory have been extensively discussed, a complete understanding of their role in cognitive control and inhibition is still elusive. Here we provide an up-to-date review on synchronisation patterns underlying behavioural inhibition, extrapolating common grounds and dissociating features with other inhibitory functions. Moreover, we suggest a schematic conceptual framework and highlight existing gaps in the literature, current methodological challenges and compelling research questions for future studies.